Security Agenda in a Risk Society: A Stable and Rational Policy, or Chaotic Securitization? - Oldrich Krulík; Libor Stejskal (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
The processes whereby security policy tackles security challenges and converts them into security priorities (at least since September 11, 2011) are criticized by experts working in the field as erratic and susceptible to media and society pressures. We are always being warned of the emergence of new threats requiring close attention of the relevant authorities and security forces, but the existing security challenges do not disappear or become less serious with such declarations. Uncontrolled securitization forces all those concerned to concentrate their efforts and resources on ever-shifting priorities, thus increasing the burden borne by national security systems. The vital question is how to build a long-term rational security agenda, flexibly accommodating the whole range of security challenges.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: 330